1988
DOI: 10.1128/aac.32.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Oral ciprofloxacin treatment for Salmonella typhimurium infection of normal and immunocompromised mice

Abstract: Oral treatment of Salmonella typhimurium infection with ciprofloxacin was compared with conventional chemotherapy with ampicillin or chloramphenicol in normal (CFW1) and immunocompromised (C57BL/6) mice. Administration of the antibiotics for 12 days reduced the number of bacteria in livers and the mortality of C57BL/6 mice significantly. Ciprofloxacin was considerably more effective than ampicillin in prolongation of the mean survival time of these mice. Similar to conventional chemotherapeutic agents, ciprofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
(53 reference statements)
0
9
1
Order By: Relevance
“…In our experiments, treated BALB/c mice did not have relapses after 5 days of treatment. The in vitro MIC for our S. dublin strain was comparable to the MIC for the S. typhimunium strain used in the earlier study (5). However, in mice S. typhimurium is more virulent than S. dublin, which may account for the increased efficacy of ciprofloxacin in our study (27).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In our experiments, treated BALB/c mice did not have relapses after 5 days of treatment. The in vitro MIC for our S. dublin strain was comparable to the MIC for the S. typhimunium strain used in the earlier study (5). However, in mice S. typhimurium is more virulent than S. dublin, which may account for the increased efficacy of ciprofloxacin in our study (27).…”
Section: Discussioncontrasting
confidence: 48%
“…S. dublin Lane pSD6 is a kanamycin-resistant derivative of the parent Lane strain in which TnS is inserted in the cryptic plasmid outside the vir region; it is fully virulent (6). Bacteria were suspended in 0.1 M NaHCO3 solution to 5 x 108 CFU/ml. A total of 0.2 ml of the suspension was delivered into the stomach by gavage.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, topical ciprofloxacin/dexamethasone therapy was found to be superior to oral amoxicillin/clavulanic acid in acute otitis media with otorrhea 22 . Literature findings also suggest that ciprofloxacin, when given orally, is superior to ampicillin and chloramphenicol in curing typhoid in immunocompromised mice 23 . Ciprofloxacin, a commonly used broad-spectrum antibiotic, has also attracted significant interest of the scientific community due to its antiproliferative and apoptotic activities in several cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo pharmacokinetic studies showed that the ciprofloxacin plasma concentration was more than 2-fold increased in Bcrp1 Quinolone antimicrobial drugs are widely used because of their broad spectrum and intense bactericidal activity. They are developed for oral and parenteral use in the treatment of bacterial diseases, including severe systemic infections (Brunner and Zeiler, 1988). Most quinolone antibacterial drugs are rapidly absorbed from the intestine, with a bioavailability of close to 90%, and then penetrate well into most body tissues and fluids.…”
mentioning
confidence: 99%
“…They are developed for oral and parenteral use in the treatment of bacterial diseases, including severe systemic infections (Brunner and Zeiler, 1988). Most quinolone antibacterial drugs are rapidly absorbed from the intestine, with a bioavailability of close to 90%, and then penetrate well into most body tissues and fluids.…”
mentioning
confidence: 99%